The Role of Human Resources in Human Capital Management - Dharma Diani, Rinny; Hamida, Hamida; Ketut R Sudiarditha, I (Siber Journal of Advanced Multidisciplinary, 2024)
This article discusses the important role of human resources (HR) in Human Capital Management (HCM) with a theoretical basis from various experts, as well as global case studies that illustrate the implementation of the role of HR in HCM. Based on the theory outlined in "Armstrong's Handbook of Human Resource Management Practice," HCM underscores the importance of managing human capital as a strategic asset that contributes to the achievement of organizational goals. Experts such as Gary Becker, David Ulrich, and Michael Armstrong state that investing in developing employee skills and knowledge is the key to increasing a company's productivity and profitability. In a global context, case studies show that the role of HR has evolved to become more strategic, not only managing employees but also adapting to current trends in human resource management. These trends include employee well-being, skills-based hiring, work flexibility, hybrid learning, ESG reporting, and interpersonal skills development. The role of HR in HCM is about transforming human resources into the main force that drives organizational growth and sustainability through effective and adaptive management strategies.